Preliminary Development of Subsumption Architecture Control for Automated Guided Vehicle - Tanaya, Prianggada Indra (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2019)
Subsumption control architecture is an control architecture based on parallel system. Input of information of sensors is directly connected through modules in the control system, and further the decision making is connected to actuators. Automated Guided Vehicle or AGV is an automated component within integrated manufacturing system. In this article, this control architecture will be designed and implemented to an AGV. Commands are designed based on Object-Oriented technology. The commands are arranged in subsumption, where a command higher subsumed other command of its lower level. GPFO (Greater Priority First Out) technique is implemed for executing the commands by using multi-threading. Experimentation is performed to have the characteristics of commands being executed. This work introduce our effort to design an operating system for an AGV.